Early Modern Thebaid : the Latin Commentary Tradition - Berlincourt, Valéry (Leiden–Boston: Brill, 2015)
Many present-day readers of Statius meet the names of early modern commentators in philological commentaries and critical apparatuses. Inevitably, their sense of what such commentators contributed to the understanding and interpretation of the poems rests mainly on exegetical statements cut from their original contexts both interpretive and historical : single notes and short utterances excerpted from larger discussions, deprived of their broader argumentative sequences, selected on the grounds of their direct relevance to those aspects that most interest a present-day commentator or editor. This paper aims at recovering something more of this important aspect of Statius’s reception, by showing how the early modern commentaries on the Thebaid can interest us, not only as valuable contributions to our own appreciation of this poem, but also as witnesses of how it was read in historical and cultural situations different from our own. It focuses on the neo-Latin commentaries from the 16th and 17th centuries, notably those of Bernartius, Gronovius, Barth and Beraldus, which contributed heavily to the later exegetical tradition and are being used most frequently nowadays, but also those of minor and now half-forgotten figures. The commentaries written in vernacular languages and/or during the next two centuries are also briefly discussed. A selection of key passages from Statius’s Theban epic allows to see how, in the early modern period, this poem provoked keen interest, ranging from emendatio (sometimes obviously related to aesthetic questions) to antiquarianism and ethics, and how commentaries dedicated to it varied according to the idiosyncratic exegetical strategies of each scholar and the changing demands of the reading audience. At a more general level, the exegetical tradition of the Thebaid is contrasted with the very different ones of the Silvae and the Achilleid.